Pengaruh Pendekatan Saintifik Pada Mata Pelajaran Fikih Terhadap Minat Belajar Siswa Kelas V MI Muhammadiyah Tegalurung - Muzfirah, Suci; Afdal, Muhammad; Mubarok, Frenky (Study Program of Madrasah Ibtidaiyah Teacher Education at Institut Agama Islam Pangeran Dharma Kusuma Indramayu, 2025)
Lack of student interest in fiqh lessons is one of the problems that occur in educational institutions. Fiqh learning in the Madrasah Ibtidaiyah curriculum is one of the subjects that is directed to prepare students for the ability to recognize, understand, appreciate, and practice Islamic law, which then becomes the basis for a way of life through guidance, teaching, training, and experience activities. This study aims to determine the effect of the scientific approach to fiqh subjects on the learning interests of class V students of MI Muhammadiyah Tegalurung. This type of research uses quantitative descriptive. To obtain the data studied, the researcher took data from the sample in this study using 1 class, namely class V A as the experimental class, the data collection method in this study used a questionnaire, while for the data analysis technique in this study using the R Square test Based on the SPSS output table